Ақпараттық қауіпсіздік кез келген құрылымның қызметі мен дамуының барлық құбылысын қамтамасыз етеді (Journal of Philosophy, Culture and Political Science, 2018)
At the moment a lot of attention gives to the problem of information security, but meanwhile attention going to technical skills of security system. In the given article information security considers as large system, that shows practical aspects of development and activity of any structure.